Disability due to spinal degenerative disorders: causes, features of dynamics, and ways of preventions - Yaremenko, Dmytro; Shevchenko, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Experts in Ukraine, USA and European countries note disability population growth due to chronic low back pain. In most cases the main cause of it are degenerative changes in vertebral structures. Purpose: to scientifically substantiate the most actual medical-organizational actions for prevention and decline of disability data due to degenerative disorders of the spine. Methods: an expert analysis of 194 disability cases in 1999-2003 and of 164 ones in 2007-2009 due to degenerative disorders of the spine is performed. The indexes of rehabilitation are analyzed. Results: among initially recognized as disabled people due to orthopedic pathology percentage of patients with the degenerative spine increased on 4,7 % and reached (35,8 ± 0,6) % in 2007-2009 versus (31,1 ± 0,6) % in 1999-2003. Among invalids with the degenerative spine percentage of young persons and people of working age increased to 88,3 % versus 74,7 % accordingly. Greater part of contingent investigated were 87,6 % patients with injuries and disorders of the lumbar spine. Percentage of patients with the degenerative cervical spine was 6,7 % in 1999-2003, and 4,3 % in 2007-2009. Percentage of disability due to generalized osteochondrosis of the spine significantly increased from 15,8 % in 2007-2009 versus 5,7 % in 1999-2003. The same concerns patients with intervertebral disks herniations (from 58,2 to 79,9 %) and protrusions (from 6,2 to 10,4 %) diagnosed in this period. Causes of primary disability in 73-78% of cases was combination of such factors as severity of the disease, defects in organization of treatment and curatively-diagnostic process, social factors and terms of way of life, complications of pathological process, secondary dysfunction of internal organs, etc. The amount of persons that did not succeed to be rehabilitated increased depending on duration of period of disability. So, the index of partial rehabilitation during the first four years diminishes annually in 1,5-2 times. Besides each year in (2,5 ± 1,3)% of patients with the degenerative spine disability group set indefinitely. More intensive process of rehabilitation indicated in patients after surgical treatment comparing to the patients conservatively treated. Conclusions: the primary task for the decline of disability index among people with the degenerative spine we consider an improvement of medical care organization for such patients. It is necessary to create the clear system of account of the patients, who need restoration treatment and rehabilitation according to individual programs as well as to standardize programs of restoration treatment.